Gestational diabetes increases preterm membrane rupture risk through elevated hydroxydesmethylpiperine sulfate levels - Li, Ying; Lin, Rong; Zhang, Tianshu; Shi, Tianyu; Ding, Xingwang; Ma, Jinqi (Frontiers in Endocrinology, 2025)
ObjectivesGestational diabetes mellitus (GDM) is a metabolic disorder that increases the risk of premature rupture of membranes (PROM). The link between GDM-associated metabolic dysregulation and PROM remains unclear. This study investigates the underlying metabolic mechanisms to identify potential therapeutic targets for improving pregnancy outcomes.MethodsThe study involved 354 mothers from the GDM Mother and Child Study (GMCS) at Wuxi People’s Hospital, Nanjing Medical University. A regression model assessed the GDM-PROM relationship. Third-trimester serum metabolites were analyzed using ultra-high-performance liquid chromatography and high-resolution mass spectrometry.ResultsA higher percentage of women with PROM were diagnosed with GDM (15.7% vs. 32.3%, P=0.005). Although no significant differences were found in 1-h and 2-h glucose levels (P=0.216 and 0.129), fasting glucose was elevated in the PROM group (4.50 [0.43] vs. 4.73 [0.71], P=0.017). Both unadjusted and adjusted models confirmed GDM as a risk factor for PROM (OR: 2.548, 95% CI: 1.341–4.759; P=0.004). After adjusting for confounders, GDM remained positively associated with PROM risk (OR: 2.538, 95% CI: 1.223–5.224; P=0.012). Hydroxydesmethylpiperine sulfate levels were significantly elevated in all study groups.ConclusionGDM elevates PROM risk by disrupting fetal membrane integrity through metabolic alterations. Elevated hydroxydesmethylpiperine sulfate levels in GDM-PROM cases indicate its potential as a PROM risk biomarker, underscoring the importance of early metabolic screening and glycemic control. Further research should explore this metabolite’s mechanisms and therapeutic potential.